Neurotoxicity evaluation of three root canal sealers on cultured rat trigeminal ganglion neurons - Er, Kursat; Ayar, Ahmet; Kalkan, Omer-Faruk; Canpolat, Sinan; Tasdemir, Tamer; Ozan, Ulku (Medicina Oral S.L., 2017)
Background: The aim of this study was to investigate the possible neurotoxic effects of 3 root canal sealers (RCSs) (AH Plus, GuttaFlow, iRoot SP) on cultured rat trigeminal ganglion (TG) neurons. Material and Methods: Primary cultures of TG neurons were obtained from 1 to 2-day old rats. Freshly mixed RCSs were incubated in sterile phosphate buffered saline and cells were incubated with supernatants of the RCSs for different time intervals (1-, 3-, 6- and 24-h; 1 or 1/10 diluted) and viability/cytotoxicity was tested by counting the number of live cells. Pair of dishes with cells from the same culture incubated with only culture medium was considered as negative controls. Cell images were captured and acquired at x200 magnification using a microscope equipped with a camera using special image program. The viable cells were manually counted assigned from the images for each dose and incubation duration. Data was analysed by using 1-way analysis of variance with Tukey post hoc tests. Results: There was no significant change in cell viability after short duration of incubation (1- and 3-h) with the supernatant of any of RCSs, except for undiluted-AH Plus at 3-h. When AH Plus was compared with other RCSs, for diluted supernatants, there was only significant difference between iRoot SP and AH Plus at 24-h (P < 0.05). Whereas undiluted-AH Plus was significantly more cytotoxic for 3-, 6- and 24-h periods as compared to respective incubation periods of undiluted other groups (P < 0.05). GuttaFlow groups had similar neurotoxic effect on cells for all test periods. Conclusions: All tested RCSs exhibited a variable degree of neurotoxicity on these primary sensory neurons of orofacial tissues, depending on their chemical compositions. GuttaFlow and iRoot SP evoked a less toxic response to TG cells than AH Plus. © Medicina Oral S. L. C.I.F. B 96689336.
Keywords: AH Plus; Cell culture; GuttaFlow; IRoot SP; Neurotoxicity; Root canal sealer; Trigeminal ganglia